An iconographic exploration of the "rattlesnake" gorgets of eastern Tennessee. Issue 2 (4th May 2018) - King, Adam; Forst, Samuel; Lewis-Lavin, Ashley; McBurnett, Richard; Rauch, Justin; Rosick, Don; Swaney, Lelan; Thompson, John
ABSTRACT: Compared to other gorget styles and themes made during the Mississippian period, the so-called rattlesnake gorgets of eastern Tennessee have been found in fairly large numbers. Stylistically, Muller assigned these gorgets to the temporally related Lick Creek and Citico styles, while Crawford's recent work has argued for substyles within. While their style has been studied extensively, the idea that these gorgets depict rattlesnakes generally has been accepted without further consideration. In this paper, we present the results of a systematic iconographic study of rattlesnake gorgets. Ultimately, we conclude that the image's original referent is not just a snake but instead is intended to be a model of the cosmos at night.